Anisotropic magnetoresistance and weak spin-orbital coupling in doped ZnO thin films - Tian, Yufeng (2013)
Both out-of-plane and in-plane anisotropic magnetoresistance (AMR) of Cu-doped ZnO thin films with different crystalline orientations are studied. Comparative data of angular dependent AMR suggest that the out-of-plane AMR comes from the geometric effect, while the in-plane AMR can be attributed to the field-dependent path-length effect. Moreover, the small magnitude of AMR and the negligible magnetocrystalline anisotropy suggest that the spin-orbit coupling in Cu-doped ZnO is relatively weak.